Impact of Ag Coating Thickness on the Electrochemical Behavior of Super Duplex Stainless Steel SAF2507 for Enhanced Li-Ion Battery Cases - Hyeongho Jo; Jung-Woo Ok; Yoon-Seok Lee; Sanghun Lee; Yonghun Je; Shinho Kim; Seongjun Kim; Jinyong Park; Jonggi Hong; Taekyu Lee; Byung-Hyun Shin; Jang-Hee Yoon; et al. (Crystals)
Li-ion batteries are at risk of explosions caused by fires, primarily because of the high energy density of Li ions, which raises the temperature. Battery cases are typically made of plastic, aluminum, or SAF30400. Although plastic and aluminum aid weight reduction, their strength and melting points are low. SAF30400 offers excellent strength and corrosion resistance but suffers from work hardening and low high-temperature strength at 700 °C. Additionally, Ni used for plating has a low current density of 25% international copper alloy standard (ICAS). SAF2507 is suitable for use as a Li-ion battery case material because of its excellent strength and corrosion resistance. However, the heterogeneous microstructure of SAF2507 after casting and processing decreases the corrosion resistance, so it requires solution heat treatment. To address these issues, in this study, SAF2507 (780 MPa, 30%) is solution heat-treated at 1100 °C after casting and coated with Ag (ICAS 108.4%) using physical vapor deposition (PVD). Ag is applied at five different thicknesses: 0.5, 1.0, 1.5, 2.0, and 2.5 μm. The surface conditions and electrochemical properties are then examined for each coating thickness. The results indicate that the PVD-coated surface forms a uniform Ag layer, with electrical conductivity increasing from 1.9% ICAS to 72.3% ICAS depending on the Ag coating thickness. This enhancement in conductivity can improve Li-ion battery safety on charge and use. This result is expected to aid the development of advanced Li-ion battery systems in the future.